Specific Inflammatory Stimuli Lead to Distinct Platelet Responses in Mice and Humans. - Lea M Beaulieu; Lauren Clancy; Kahraman Tanriverdi; Emelia J Benjamin; Carolyn D Kramer; Ellen O Weinberg; Xianbao He; Samrawit Mekasha; Eric Mick; Robin R Ingalls; Caroline A Genco; Jane E Freedman (PLoS ONE)
Introduction Diverse and multi-factorial processes contribute to the progression of cardiovascular disease. These processes affect cells involved in the development of this disease in varying ways, ultimately leading to atherothrombosis. The goal of our study was to compare the differential effects of specific stimuli--two bacterial infections and a Western diet--on platelet responses in ApoE-/- mice, specifically examining inflammatory function and gene expression. Results from murine studies were verified using platelets from participants of the Framingham Heart Study (FHS; n = 1819 participants). Methods Blood and spleen samples were collected at weeks 1 and 9 from ApoE-/- mice infected with Porphyromonas gingivalis or Chlamydia pneumoniae and from mice fed a Western diet for 9 weeks. Transcripts based on data from a Western diet in ApoE-/- mice were measured in platelet samples from FHS using high throughput qRT-PCR. Results At week 1, both bacterial infections increased circulating platelet-neutrophil aggregates. At week 9, these cells individually localized to the spleen, while Western diet resulted in increased platelet-neutrophil aggregates in the spleen only. Microarray analysis of platelet RNA from infected or Western diet-fed mice at week 1 and 9 showed differential profiles. Genes, such as Serpina1a, Ttr, Fgg, Rpl21, and Alb, were uniquely affected by infection and diet. Results were reinforced in platelets obtained from participants of the FHS. Conclusion Using both human studies and animal models, results demonstrate that variable sources of inflammatory stimuli have the ability to influence the platelet phenotype in distinct ways, indicative of the diverse function of platelets in thrombosis, hemostasis, and immunity.